Incidence of ventilator associated pneumonia and drug-resistant bacterial preponderance: a fact to ponder - Asir, Johny G.; Jayasekaran, Vidya; Shanmugam, Vadivu; Elan, Sujitha; Kanungo, Reba (International Journal of Research in Medical Sciences, 2018)
Background: Management of ventilator-associated pneumonia (VAP) in critically ill patients is a challenge to intensivists. This study aimed at identifying microbial factors and infection control practices that influenced incidence of VAP in a tertiary care hospital. Methods: Incidence of VAP among patients admitted to the intensive care units (ICU) from January to December 2016 was estimated. A one year period of study was divided into 3 segments of January to April, May to August, and September to December. Isolation rates of Gram Negative Bacteria (GNB) from respiratory samples and their extensively drug resistance (XDR) pattern were also analyzed. Results: A total of 14 patients had developed VAP. Incidence of VAP in the 1st, 2nd and 3rd segments of the year was 25.3, 15.2 and 4.1/1000 ventilator days respectively. Acinetobacter baumannii was the causative agent in all patients (100%). Among all GNB isolated the rate of Acinetobacter baumannii was 83%, 64%, 59% during the 3 segments of the year. XDR strains were 76%, 62% and 55%. Interventional factors like improvement in infection control practices which included hand hygiene, cohorting of MDR/XDR infected patients and environmental surveillance was noted. Conclusions: The VAP incidence declined in the later part of the year than the earlier (25.3 Vs 4.1/1000 ventilator days), with a notable decrease in the isolation of Acinetobacter baumannii (p value-0.005) and XDR organisms (p value-0.01). Directly proportionate association of VAP incidence with microbial factors were noted. Infection control measures to curtail MDR organisms should be an important component in the management of patients on ventilators.